Analisis Hasil Belajar Siswa Kelas Unggulan Berdasarkan Taksonomi Bloom Revisi Domain Kognitif Pada Materi Pythagoras - Putri Hapsari, Elviana; , Rita P. Khotimah, S. Si., M. Sc (2017)
Excellent class student's cognitive ability is quite diverse. It affects student learning outcomes. It is important to know how the cognitive abilities of students so that teaching and learning process is optimal. This study aimed to describe and analyze student's learning outcomes based on cognitive domain of revised bloom's taxonomy in the subject pythagoras. This type of research is qualitative descriptive. This subject of research is 3 eighth-H grade students of SMP Negeri 1 Boyolali, consisting of one student of higher order thinking, one student of lower order thinking and one student in middle level between the two. Data collection techniques used were test results regarding the subject Pythagoras, interviews and documentation. The validity of the data using triangulation techniques. Data analysis technique is done through data reduction, data presentation, and conclusion. The results showed that remember indicators can only be achieved by students S1, while students S2 and S3 can not reach the indicator. Understand indicators can be achieved by the students S1 and S2, while students S3 can not reach the indicator. Apply indicators can be achieved by three subjects, namely students S1, S2 and S3. Analyze indicators can be achieved by students S1 and S2, while students S3 can not reach the indicator. Evaluate indicators can only be achieved by students S1, while students S2 and S3 can not reach the indicator. Create indicators can be achieved by students S1 and S2, while students S3 can not reach the indicator.